Assessment of Community's Perception Toward Single-Use Plastic Shopping Bags and Use of Alternative Bags in Jimma Town, Ethiopia. (March 2022) - Misgana, Bikila; Tucho, Gudina Terefe
Background: The use of plastic shopping bags increases and poses tremendous pressure on the local environment. However, little is known about its utilization among different population categories and their perception of its utilization and willingness to use other sustainable alternatives. This study aimed to assess the community's perception toward the use of plastic shopping bags and its options in Jimma town, Ethiopia Methods: A community-based descriptive cross-sectional study design was conducted on 351 customers and retailers selected from the town's main marketing areas. The data was collected using a structured questionnaire in a face-to-face interview and analyzed using SPSS v.21. Results: The results show that all the respondents use plastic shopping bags for different shopping services. The majority (147 (41.9%)) of the respondents said that they use 5 to 10 shopping bags, and 66 (18.8%) use more than 10 shopping bags per week. Participants responded with different reasons for the frequent use of plastic bags for shopping. Accordingly, 116 (33.0%) responded that plastic bags are cheap, 92 (26.2%) use them due to lack of alternatives, and 89 (25.4%) responded that plastic bags are light and convenient to use. However, 326 (93%) of the respondents support efforts to reduce single-use plastic bags, 284 (80.9%) support a ban on single-use plastic bags, and 319 (90%) were willing to pay for alternative shopping bags. Conclusion: Communities are aware of the environmental problems associated with the intensive use of plastic shopping bags, their wastes, and the need for alternative options. However, it will continue to pose significant environmental challenges unless low-cost and environment-friendly alternative options are available.